PENAFSIRAN GULUL DALAM AL-QUR’AN: TELAAH SURAT ALI IMRAN AYAT 61 PADA TAFSIR KEMENTERIAN AGAMA RI - Oki Dwi Rahmanto; Muhammad Anwar Idris (UIN Mataram, 2021)
One of the works of many interpretations owned by Indonesia is Interpretation Al-Qur'an Thematic Ministry of Religious. The interpretation of the word gulu>lin surah A>li ‘Imra>n verse 161 researchers think is suitable if interpreted using the interpretation of the Ministry of Religious Affairs. Considering that this interpretation is a work of interpretation that follows the development of science and technology, and is systematically organized based on actual themes in the community that can answer various people's problems, this research is qualitative using scripted-analysis methods. The findings of the first researcher, said gulu>lin letter A>li ‘Imra>n verse 161 were initially only interpreted by treason in the division of the spoils of war. But in the interpretation of the Book of Interpretation of the Ministry of Religious Affairs of the Republic of Indonesia contested the word gulu>lwith a broader meaning such as corruption. Second, the interpretation of gulu>ll is very relevant to the current conditions that exist in Indonesia with the phenomenon of corruption, bribery, officials who abuse their positions for personal purposes that can harm the people.